A transvaginal probe for near infrared spectroscopic monitoring of the bladder detrusor muscle and urethral sphincter. Issue 6 (2008) - Shadgan Shadgan, Babak Babak; Stothers Stothers, Lynn Lynn; Macnab Macnab, Andrew Andrew
Abstract : The majority of in vivo applications of near infrared spectroscopic (NIRS) monitoring use transcutaneous optode placement over the tissue of interest. Invasive application of optodes is occasionally described for monitoring tissue too deep for transcutaneous study, principally in animal models, but sometimes in humans. Invasive fibre-optic probes have been developed for a range of other spectroscopic applications including some in vivo . We describe the design and feasibility testing in a human subject of a vaginal probe to extend the scope of recently developed techniques for NIRS monitoring in urology. Design criteria included: use of optodes and cables with dimensions compatible with appropriate overall probe size; dual channel capability (for simultaneous monitoring of bladder wall and urethral sphincter); secure interoptode separation at correct distance for required penetration; ease of insertion, orientation and avoidance of movement artifact. Components were obtained that met design criteria and allowed use of the probe connected to a commercial NIRS instrument. Iterative development established optimal interoptode distance and secure positioning of a probe that could be housed for in vivo study within a disposable vaginal speculum. The feasibility of monitoring changes in chromophore concentration in the bladder detrusor and urethral sphincter using this intravaginal probe was evident from four separate studies during voiding and a series of physiologic events (cough, Valsalva and Kiegel contractions) in a healthy female volunteer. This small series suggests that reproducible data free of movement artifact, with consistent patterns and magnitudes of chromophore change can be obtained with the probe designed.